Patai's Chemistry of Functional Groups 2014
DOI: 10.1002/9780470682531.pat0885
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Hydrogen Peroxide for Disinfection and Sterilization Applications

Abstract: Hydrogen peroxide is a widely used antimicrobial chemical. It is used in both liquid and gas form for preservative, disinfection and sterilization applications. Its advantages include its potent and broad spectrum antimicrobial activity, flexibility in use, and safety profile in comparison to other microbiocides. Hydrogen peroxide has been shown to be effective against all forms of microorganisms, including dormant forms with known high resistance such as bacterial spores and protozoal cysts, and also infectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
115
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(116 citation statements)
references
References 27 publications
0
115
0
1
Order By: Relevance
“…The high antimicrobial activity and the broad spectrum of the hydrogene peroxide vapour have been proven by a number of scientific studies (19). Boyce at al., (20) and Barbut at al.,(21) have found that hydrogen peroxide vapour has good sporicidal activity and leads to complete inactivation of Clostridium difficile spores regardless of strain and/or surface.…”
Section: Discussionmentioning
confidence: 99%
“…The high antimicrobial activity and the broad spectrum of the hydrogene peroxide vapour have been proven by a number of scientific studies (19). Boyce at al., (20) and Barbut at al.,(21) have found that hydrogen peroxide vapour has good sporicidal activity and leads to complete inactivation of Clostridium difficile spores regardless of strain and/or surface.…”
Section: Discussionmentioning
confidence: 99%
“…Future studies will focus on the identification of natural, non-antibiotic prophage inducers. For example, hydrogen peroxide is already used as an antimicrobial to control the presence of bacterial pathogens in foods (McDonnell, 2014), and has been shown to cause DNA damage mediated prophage induction (Los et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Once integrated, prophages remain dormant until the cell experiences some form of stress, which will then induce the phages to activate their lytic cycle, replicate and lyse their host cell (Oppenheim, Kobiler, Stavans, Court, & Adhya, 2005). Different forms of stress that have been reported to induce prophages include hydrogen peroxide, ultraviolet light, and antibiotics, such as mitomycin C and streptonigrin (Cao et al, 2012;Gerner-Smidt, Rosdahl, & Frederiksen, 1993;Gervasi, Curto, Narbad, & Mayer, 2013;Horgan et al, 2010;Lan et al, 2009;Levine & Borthwick, 1963;Los, Los, Wegrzyn, & Wegrzyn, 2010;McDonnell, 2014;Mmolawa, Willmore, Thomas, & Heuzenroeder, 2002;Muschel & Schmoker, 1966;Pryshliak, Hammerl, Reetz, Strauch, & Hertwig, 2014;Wallin-Carlquist et al, 2010;Wormser & Pardee, 1957;Yee, De Grandis, & Gyles, 1993). In this study, cell lysis through induction of prophages was investigated as a novel approach to control bacterial pathogens on fresh produce.…”
Section: Introductionmentioning
confidence: 99%
“…It also has advantages with regard to its toxicity and environmental profile. The general mechanisms of action of H 2 O 2 significantly reduce any risk of development of resistance to the biocide over time, unlike many other types of anti-infective drugs or biocides [15] .…”
Section: This Is An Open Access Article Distributed Under the Creativmentioning
confidence: 99%